Synthesis of novel chiral pyrrolidine-type (salen)Mn(III) complexes. - Weiqiang Zhang (2006)
The thesis reports the total syntheses of new chiral pyrrolidine-type salen ligands 5.4 and their corresponding Mn(III) complexes 5.5. The salen ligands were synthesized by condensation of tras-(3R,4R)-diaminopyrrolidine (3.12) or trans-(3R,4R)-1-benzyl-3,4-diaminopyrrolidine (3.10) with two equivalents of (R)-3-formyl-2-hydroxy-2'-phenyl-1,1'-binaphthalene [(R)-4.9]. The salen ligands were transformed to their corresponding Mn(III) complexes following a general procedure. The catalytic performances of the synthesized (salen)Mn(III) complexes in asymmetric epoxidation of 1,2-dihydronaphthalene were tested. In chapter 1, a review of asymmetric epoxidation of alkenes is given. Emphasis is placed on the development and some of the important designs of chiral salen ligands and their corresponding (salen)Mn(III) complexes. In chapter 2, the nature of the research project is outlined. In chapter 3, the syntheses of trans-(3R,4R)-diaminopyrrolidine trihydrochloride salt (3.9), trans-(3R,4R)-1-benzyl-3,4-diaminopyrrolidine (3.10) and its trihydrochloride salt (3.11) are reported. These compounds were prepared from (2R,3R)-(-i-)-tartaric acid via multi-step syntheses. Extensive studies on optimization of these transformations are reported. Chapter 4 records the synthesis of (R)-3-formyl-2-hydroxy-2'-phenyl-1,1'-binaphthalene [(R)-4.9] from 2-naphthol via a seven-step synthetic procedure. Extensive studies on these transformations are described, especially on the oxidative coupling of 2-naphthol and on the optical resolution of racemic 2,2'-dihydroxy-1,1'-binaphthalene. In chapter 5, the preparations of salen ligands 5.4 and their corresponding Mn(III) complexes 5.5 are reported. The applications of synthesized Mn(III) complexes in asymmetric epoxidation of 1,2-dihydronaphthalene were carried out. In chapter 6, an overall conclusion of the work is given.